2013
DOI: 10.1111/jdi.12133
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin gene variants, adiponectin isoforms and cardiometabolic risk in type 2 diabetic patients

Abstract: Aims/Introduction: The aim of the present study was to examine the associations of rs2241766 (+45T>G), rs1501299 (+276G>T), rs17300539 (-11391G>A) and rs182052 (-10069G>A) in the adiponectin (Ad) gene with adiponectin concentrations, and concomitantly the association of these variants with cardiometabolic risk in type 2 diabetic patients of African ancestry. Materials and Methods: A cross-sectional study of 200 patients was carried out. Concentrations of total, high (HMW), middle (MMW) and low (LMW) molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…A recent meta-analysis concluded that there was a strong association between Ad rs266729 and cardiovascular disease ( 33 ). In agreement with previous studies, Foucan et al ( 34 ) showed that French patients carrying the Ad rs2241766 G allele had an increased risk of CAD. Other studies have reported discordant findings because of differences in ethnicity, phenotypes, and environments ( 16 , 33 ).…”
Section: Discussionsupporting
confidence: 92%
“…A recent meta-analysis concluded that there was a strong association between Ad rs266729 and cardiovascular disease ( 33 ). In agreement with previous studies, Foucan et al ( 34 ) showed that French patients carrying the Ad rs2241766 G allele had an increased risk of CAD. Other studies have reported discordant findings because of differences in ethnicity, phenotypes, and environments ( 16 , 33 ).…”
Section: Discussionsupporting
confidence: 92%
“…Decreased plasma adiponectin levels were observed in patients with metabolic syndrome, diabetes mellitus, dyslipidaemia and obesity [7]. Previous studied suggest also significant associations between adiponectin gene polymorphisms and diabetes mellitus, metabolic syndrome, and obesity [8,9]. The aim of this study was to examine the association between adiponectin and leptin gene polymorphisms and the development of gestational diabetes.…”
Section: Introductionmentioning
confidence: 91%
“…The rs2241766 polymorphism is a T/G substitution in exon2 and the rs1501299 is a G/T substitution in intron2. The influence of the two SNPs on CAD have been investigated in patients with T2DM, [ 15 17 ] the results are inconsistent. In the study of Bacci et al [ 18 ] and Filippi et al[ 19 ], no association was found between the rs2241766 polymorphism and CAD risk in T2DM patients.…”
Section: Introductionmentioning
confidence: 99%